2020
DOI: 10.3201/eid2611.200960
|View full text |Cite
|
Sign up to set email alerts
|

High Dengue Burden and Circulation of 4 Virus Serotypes among Children with Undifferentiated Fever, Kenya, 2014–2017

Abstract: Little is known about the extent and serotypes of dengue viruses circulating in Africa. We evaluated the presence of dengue viremia during 4 years of surveillance (2014–2017) among children with febrile illness in Kenya. Acutely ill febrile children were recruited from 4 clinical sites in western and coastal Kenya, and 1,022 participant samples were tested by using a highly sensitive real-time reverse transcription PCR. A complete case analysis with genomic sequencing and phylogenetic analyses was conducted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 33 publications
2
43
0
Order By: Relevance
“…The findings from previous studies [ 90 , 91 ] show that co-morbidities increase the risk of severe disease and fatal outcomes among dengue patients. Our results show that in the past decade (2010–2020), malaria and dengue co-infections were the most prevalent, followed by dengue and chikungunya co-infection [ 24 , 31 , 40 , 43 , 53 , 56 , 79 , 92 , 93 , 94 , 95 ]. A similar occurrence pattern of malaria and dengue co-infection dominance followed by dengue and chikungunya co-infection was previously reported [ 96 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The findings from previous studies [ 90 , 91 ] show that co-morbidities increase the risk of severe disease and fatal outcomes among dengue patients. Our results show that in the past decade (2010–2020), malaria and dengue co-infections were the most prevalent, followed by dengue and chikungunya co-infection [ 24 , 31 , 40 , 43 , 53 , 56 , 79 , 92 , 93 , 94 , 95 ]. A similar occurrence pattern of malaria and dengue co-infection dominance followed by dengue and chikungunya co-infection was previously reported [ 96 ].…”
Section: Discussionmentioning
confidence: 93%
“…Spill-over of sylvatic DENV-2 strains from forest Aedes mosquitoes into a human transmission cycle possibly facilitates the spread into urban or new geographical areas with the potential to cause epidemics [ 85 , 86 ]. Further, increasing recognition of DENV as the cause of undifferentiated febrile syndromes [ 87 ], and the availability of more sensitive and specific molecular-based laboratory tests in the past decade, may have contributed to more detection and reporting of DENV serotypes [ 51 , 56 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since DENV is heavily underreported in the region, all enrolled participants were tested for dengue and malaria. In a study of undifferentiated fever in Kenya between 2014–2017, 150 (51.5%) of 291 participants with dengue viremia were malaria smear positive, suggesting a large overlap in infections [ 38 ]. Additionally, flaviviruses, which include West Nile virus (WNV), ZIKA virus (ZIKAV), and yellow fever virus (YFV), have the potential to cross-react with DENV.…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, dengue outbreaks have been recorded more frequently in many countries including Gabon, Angola, Mozambique, Kenya, Ethiopia, Sudan and Burkina Faso (6)(7)(8). All four DENV serotypes have been widely reported across Africa and the co-circulation of two or more serotypes, first reported from Gabon in 2013 ( 8) is becoming more common, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…All four DENV serotypes have been widely reported across Africa and the co-circulation of two or more serotypes, first reported from Gabon in 2013 ( 8) is becoming more common, e.g. Kenya (7), Burkina Faso (6), Nigeria (9), Tanzania (10) raising fears that severe dengue will be seen more frequently in future outbreaks in Africa.. In Cameroon numerous studies over the past twenty years have reported seroprevalence rates in rural and urban areas in Cameroon, with no major outbreak notifications (11,12).…”
Section: Introductionmentioning
confidence: 99%